Comparison of Microleakage Between Bulk-Fill Flowable and Nanofilled Resin-Based Composites. - AlSagob, Eman. (2017)
Abstract: Objectives The objective of this study was to compare the marginal leakage (silver nitrate uptake) of nanohybrid resin-based composite (RBC) and two bulk-fill flowable RBCs using specific clinical protocols. Materials and Methods Forty-eight samples in 24 extracted intact human molars were mounted in autopolymerizing acrylic resin. Class II box preparations were prepared on both mesial and distal surfaces. Then the teeth were randomized in four groups. In group 1, teeth were restored with Filtek Supreme Ultra Universal Restorative, 3M ESPE incrementally, 2 mm per increment and cured for 20 seconds per increment, to serve as a control group. In group 2, teeth were restored in 4-mm bulk with Filtek Supreme Ultra Universal Restorative and cured for 20 seconds. In group 3, teeth were restored in 4-mm bulk with Filtek Supreme Flowable Restorative and cured for 20 seconds. In group 4, teeth were restored in 4-mm bulk with SureFil SDR flow DENTSPLY, and cured for 20 seconds. Teeth were kept in distilled water throughout the investigation to prevent dehydration, and all cavities were prepared and restored by one operator. Then, all the samples were thermocycled for 2000 cycles between water baths at 5°C and 55°C with a 30-second dwell time to resemble aging of the restoration in the oral environment, and then were embedded in silver nitrate to detect microleakage. Next, the teeth were immersed into a solution of 50 wt% ammoniacal silver nitrate for 24 hours, followed by 8 hours in photo-developing solution. Finally, teeth were sectioned, and specimens' microleakage was analyzed with a stereomicroscope (20x); microleakage was calculated by dividing the dye penetration from the outer margin over the total surface of the restoration. Results One-way analysis of variance revealed significance differences between the groups in term of microleakage (p-value = 0.007) and dye penetration (p-value = 0.006). Both group 3 and group 1 showed the least microleakage, with a mean (standard deviation) of 1.90 (4.59) and 1.99 (2.24), respectively, followed by group 4, with a mean of 3.91 (6.63). Finally, group 2 showed the highest microleakage, with a mean of 8.02 (4.01). The Mann-Whitney-Wilcoxon test revealed significantly higher gingival microleakage compared with occlusal microleakage (p-value = 0.016). Gingival microleakage was found in 45.00% of the restorations versus occlusal microleakage in 18.75% of the restorations. Conclusions Filtek Bulk Fill Flowable Restorative and Filtek Supreme Ultra Universal Restorative when placed in 2-mm increments have results superior to those of conventional nanohybrid RBC when placed in 4-mm bulk. While SureFil SDR flow did not have significantly higher microleakage, it also did not significantly have less microleakage than that seen with 4-mm bulk of the conventional nanohybrid composite.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Posthodontics.; Advisors: David Bardwell, and Ala Ali.; Committee: Samer Khayat, and Paul Stark.; Keyword: Dentistry.